Long-term air pollution exposure, habitual physical activity, and incident chronic kidney disease - Zhi-Hao Li; Wei-Qi Song; Cheng-Shen Qiu; Hong-Min Li; Xu-Lian Tang; Dong Shen; Pei-Dong Zhang; Xi-Ru Zhang; Jiao-Jiao Ren; Jian Gao; Wen-Fang Zhong; Dan Liu; et al. (Ecotoxicology and Environmental Safety, 2023)
Both air pollution and physical inactivity contribute to the increased risk of incident chronic kidney disease (CKD). However, the detrimental effects of air pollution exposure could be augmented by an elevated intake of air pollutants during exercise. In the present study, we analyzed 367,978 participants who were CKD-free at baseline (2006–2010) based on the UK Biobank. Air pollutants included fine particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), and nitrogen oxides (NOX). Physical activity (PA) was obtained by the self-reported questionnaire. Using Cox proportional hazards models, hazard ratios (HRs) for incident CKD related to air pollution, PA, and incident CKD were evaluated. During a median of 12.4 years of follow-up, 14,191 incident CKD events were documented. High PM2.5, PM10, NO2, and NOX increased CKD risks by 11 %, 15 %, 14 %, and 12 %, respectively, while moderate and high PA reduced CKD risks by 18 % and 22 %, respectively. Participants with high PA and low air pollution exposure had 29 %, 31 %, 30 %, and 30 % risks of incident CKD than those with low PA and high air pollution exposure for the four air pollutants, with multivariable-adjusted HRs of 0.71 (95 % confidence intervals [CI]: 0.65–0.76) for PM2.5, 0.69 (95 % CI: 0.64–0.75) for PM10, 0.70 (95 % CI: 0.64–0.75) for NO2, and 0.70 (95 % CI: 0.64–0.75) for NOX. No clear interactions were observed between each air pollutant exposure and PA (all P for interaction > 0.05). The findings that reducing air pollution exposure and increasing PA were both independently correlated with a diminished risk of incident CKD suggest that PA could be targeted to prevent CKD generally regardless of air pollution levels. Further research is needed in areas polluted moderately and severely to examine our findings.